Preparation method of photocatalytic antibacterial spray for skin wound infection as well as product and application of photocatalytic antibacterial spray

By combining natural polysaccharides with ZIF-8@H-MPB composite nanoparticles, a photocatalytic antibacterial spray for skin wounds was prepared, which solved the problem of poor effect of traditional dressings in dealing with irregular wounds, and achieved efficient antibacterial and real-time monitoring.

CN119499370AActive Publication Date: 2025-02-25CHONGQING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411421914.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing skin dressings are not effective when dealing with irregular and large wounds, and traditional antibacterial materials are difficult to achieve real-time monitoring and efficient antibacterial.

Method used

Photocatalytic antibacterial sprays were prepared by combining natural polysaccharides with ZIF-8@H-MPB composite nanoparticles. The nanoparticles were used to generate ROS under sunlight to enhance antibacterial ability, and real-time monitoring was achieved through optical changes caused by bacterial metabolism.

Benefits of technology

It achieves effective coverage and antibacteriality of irregular wounds, promotes wound healing, and has real-time monitoring functions, reducing the use of antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499370A_ABST
    Figure CN119499370A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a photocatalytic antibacterial spray for skin wound infection as well as a product and application of the photocatalytic antibacterial spray, and belongs to the technical field of preparation of antibacterial materials. The photocatalytic antibacterial spray (BC-CS-ZHP antibacterial spray) for skin wound infection, disclosed by the invention, has the following advantages: (1) in the preparation process, Prussian blue nanoparticles (PB) and optical change generated by reduction reaction of bacterial metabolism are adopted, so that the antibacterial process can be dynamically monitored; (2) compared with traditional dressings such as hydrogel and gauze, the prepared spray form can better adapt to irregular wound shapes; (3) the prepared antibacterial spray utilizes sunlight to generate ROS (reactive oxygen species) so as to realize efficient antibiosis, and zinc ions released by nano-particles and oxidized bacterial cellulose form metal coordinate bonds, so that the mechanical property of the antibacterial spray after film formation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of antibacterial materials, and relates to a preparation method of a photocatalytic antibacterial spray for skin wound infection, a product and an application thereof. Background Art

[0002] Judging from the development trend of global medical dressings, the downstream market has an increasing demand for multifunctional, new material, and high value-added medical dressings, and more and more traditional cotton gauze is being replaced by new high-end medical dressings. Wound dressings play a significant role in the process of wound healing, mainly covering damaged skin, maintaining the moist environment and suitable temperature required for healing, providing physical and microbial protection, absorbing excess tissue fluid and relieving pain. The surface design of general antibacterial materials can start from the key factors of resisting bacterial adhesion on the surface of the material, resisting various effects of biofilms, and long-term antifouling, intelligent self-cleaning, triggered killing, bacterial capture, bacterial targeting and other strategies. According to the material, it can be divided into gauze dressings, film dressings, foam dressings, tape dressings, hydrogel dressings and other types.

[0003] Although many skin dressings such as gauze and medical cotton have been used clinically as treatment methods, their stimulating effect on wound healing is not obvious and the treatment effect is not ideal. Although a variety of antibacterial dressings have been used clinically, due to the diversity and complexity of skin wound shapes, it is difficult to form a shape that conforms to the wound and has a good adhesion effect. Hydrogels may also adhere to certain wounds, resulting in damage to the surrounding fragile skin when torn off. Especially for large and irregular wounds, the application of antibacterial dressings such as hydrogels and gauze is hindered.

[0004] Damaged skin is easily invaded by bacteria, so it is particularly important to monitor wound infection. Traditional skin wound monitoring methods are not only time-consuming, but also have limitations on monitoring instruments. Therefore, it is very necessary to invent an antibacterial spray that can adapt to different skin wounds, visualize wound healing, effectively kill bacteria, and observe bacterial infection in real time.

[0005] Natural polysaccharides have better biocompatibility and can form a denser structure through cross-linking. Chitosan, sodium alginate, cellulose, etc. are also widely used to prepare wound dressings. In addition, Prussian blue nanoparticles (PB) can act as an "indicator" in the material, and the time to replace the auxiliary material and the situation of wound infection can be determined by color change. On the other hand, PB not only has photothermal properties but also exhibits POD enzyme activity under acidic conditions, and CAT enzyme and SOD enzyme activity under neutral and alkaline conditions. Therefore, PB is modified into a hollow mesoporous structure to increase its surface area, improve light reflection, increase its enzyme-like activity, and reduce the ROS generated by ZIF-8 during the antibacterial process. The use of hollow mesoporous Prussian blue (H-MPB) as a photothermal accelerator coupled with ZIF-8 enables the material to enhance the antibacterial effect by solar light irradiation. At the same time, the release of zinc ions can not only promote fibroblast migration, angiogenesis, collagen deposition and granulation tissue formation, accelerate wound healing, but also form metal coordination bonds with the carboxyl groups in oxidized BC to improve the cross-linking degree of the composite membrane.

[0006] In summary, further research has expanded the content of PB color indication in the biomedical field. The nanoparticles formed by coupling H-MPB and ZIF-8 can produce photothermal effects under sunlight to enhance antibacterial ability, providing a new and promising strategy for the diagnosis and treatment of bacterial infections in wounds. It has good tissue penetration depth and low side effects, reducing the abuse of antibiotics in the treatment of wound infections; at the same time, it gives the material dynamic monitoring, promotes wound healing, and has good biocompatibility and antibacterial ability. Summary of the invention

[0007] In view of this, one of the objects of the present invention is to provide a photocatalytic antibacterial spray for skin wound infection; a second object of the present invention is to provide a method for preparing the photocatalytic antibacterial spray for skin wound infection; a third object of the present invention is to provide an application of the photocatalytic antibacterial spray for skin wound infection in the antibacterial and repair of skin wounds.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] 1. A method for preparing a photocatalytic antibacterial spray for skin wound infection, the preparation method comprising the following steps:

[0010] A TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added and stirred at room temperature to obtain a carboxyl activation solution, and an acetic acid solution of a natural polysaccharide is added and stirred at room temperature for 18 to 24 hours to react to form a BC-CS solution. After the reaction is completed, the solution is dialyzed and the ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are added. The solution is stirred at room temperature overnight to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray).

[0011] Preferably, the ZIF-8@H-MPB composite nanoparticles (ZHP) are prepared according to the following method:

[0012] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): adding polyvinyl pyrrolidone (PVP) and potassium ferrocyanide trihydrate into a hydrochloric acid solution, stirring to dissolve them to form a clear and transparent mixed solution, heating the solution and centrifuging to obtain Prussian blue nanoparticles (PB), further mixing the solution with polyvinyl pyrrolidone (PVP) and stirring to dissolve them in a hydrochloric acid solution, heating the solution and centrifuging to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB);

[0013] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): Dissolve polyvinyl pyrrolidone (PVP) in methanol, add the hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1), stir to disperse them evenly, then add zinc nitrate hexahydrate and 2-methylimidazole (2-Mel), stir for 6 to 12 hours and then centrifuge and wash to obtain ZIF-8@H-MPB composite nanoparticles (ZHP).

[0014] Further preferably, in step (1), the mass molar ratio of the polyvinyl pyrrolidone (PVP) to potassium ferrocyanide trihydrate is 7.5:1, g:mmol, and the mass ratio of the Prussian blue nanoparticles (PB) to polyvinyl pyrrolidone (PVP) is 1:5.

[0015] Further preferably, in step (1), the temperature of the heating reaction during the preparation of Prussian blue nanoparticles (PB) is 80°C and the time is 20 hours, and the temperature of the reaction between Prussian blue nanoparticles (PB) and polyvinyl pyrrolidone (PVP) is 140°C and the time is 4 hours.

[0016] Further preferably, in step (2), the mass ratio of polyvinyl pyrrolidone (PVP), hollow mesoporous Prussian blue nanoparticles (H-MPB), zinc nitrate hexahydrate and 2-methylimidazole (2-Mel) is 60:8:12.8-25.6:3.5.

[0017] Preferably, the mass ratio of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) in the carboxyl activation solution is 16:228.2:112.79.

[0018] Preferably, the volume mass ratio of the carboxyl activation solution, the natural polysaccharide in the acetic acid solution of chitosan (CS) and the ZIF-8@H-MPB composite nanoparticles (ZHP) is 100-120:0.5-2:1x10 -4 ~5x10 -4 , ml:g:g.

[0019] Preferably, the natural polysaccharide is any one or both of bacterial cellulose and chitosan (CS).

[0020] 2. The photocatalytic antibacterial spray for skin wound infection prepared by the above preparation method.

[0021] 3. Application of the above-mentioned photocatalytic antibacterial spray for skin wound infection in the antibacterial and repair of skin wounds.

[0022] The beneficial effects of the present invention are as follows: the present invention discloses a photocatalytic antibacterial spray for skin wound infection and a preparation method thereof, mainly using natural polysaccharide and ZIF-8@H-MPB composite nanoparticles (ZHP) to prepare a photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray), which has antibacterial, wound healing, sunlight-triggered and real-time monitoring multifunctional skin dressing, and has monitoring-treatment dual functions. On the one hand, when the spray is sprayed on the wound, it can fit on the skin surface to form a protective film covering the wound, effectively reducing the external stimulation of the wound, and the Zn released by the nanoparticles 2+Promote wound healing and regeneration. At the same time, ZIF-8@H-MPB nanoparticles generate ROS under the triggering of sunlight to enhance antibacterial ability, which can effectively treat wound infection. On the other hand, the metabolic process of bacteria will affect the redox reaction of Prussian blue to produce optical changes visible to the naked eye, thereby achieving the effect of monitoring, and the dressing can also be regularly replaced according to the change of the color of the dressing. In addition, the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in the present invention has the following advantages: (1) The optical changes produced by the reduction reaction of Prussian blue nanoparticles (PB) and bacterial metabolism used in the preparation process can realize the dynamic monitoring of the antibacterial process; (2) The prepared spray form can better adapt to irregular wound shapes compared with traditional dressings such as hydrogels and gauze; (3) The prepared antibacterial spray uses sunlight to generate ROS to achieve high-efficiency antibacterial, and the zinc ions released by the nanoparticles form metal coordination bonds with the oxidized bacterial cellulose to improve its mechanical properties after film formation.

[0023] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0025] Figure 1 A is the tensile properties of different BC-CS composite films prepared in the comparative examples after film formation, and B is the tensile properties of chitosan (CS), the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) prepared in Example 1, and the BC-CS composite film (BC-CS) prepared in Comparative Example 2 after film formation;

[0026] Figure 2 To compare the adhesion properties of different BC-CS composite films prepared in Examples 1 to 3 after film formation;

[0027] Figure 3 To compare the swelling properties of different BC-CS composite membranes prepared in Examples 1 to 3 after film formation;

[0028] Figure 4 The antibacterial properties of ZIF-8@H-MPB composite nanoparticles (ZHP) and hollow mesoporous Prussian blue (H-MPB) prepared in Example 1 at different concentrations under visible light;

[0029] Figure 5 To compare the color indication effects of the modified H-MPB nanoparticles (BC-CS@HP) prepared in Example 4 and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) after film formation in Example 3. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0031] Example 1

[0032] A photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray), the specific preparation method is as follows:

[0033] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5 g of polyvinyl pyrrolidone (PVP) and 329.25 mg of potassium ferrocyanide trihydrate were added to 100 ml of hydrochloric acid solution, stirred to dissolve to form a clear and transparent mixed solution, heated to 80° C. for 20 h, and centrifuged to obtain Prussian blue nanoparticles (PB). 0.02 g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1 g of polyvinyl pyrrolidone (PVP), stirred and dissolved in 20 ml of hydrochloric acid solution, heated to 140° C. for 4 h, and then centrifuged and washed to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB);

[0034] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinyl pyrrolidone (PVP) was dissolved in 12 ml of methanol, and 8 mg of the hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added, and after stirring to make it evenly dispersed, 12.8 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazole (2-Mel) were added. After stirring for 6 hours, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (specific reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452 (2023) 138562);

[0035] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 112.79 mg of N-hydroxysuccinimide (NHS) were stirred at room temperature to obtain carboxyl-activated powder, and an acetic acid solution of natural polysaccharides (the acetic acid solution of natural polysaccharides contained 1 g of bacterial cellulose and 1 g of polysaccharide (CS)) was added and stirred at room temperature overnight to form a BC-CS solution. After the reaction was completed, the solution was dialyzed and 1×10 -4 g The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped, stirred overnight at room temperature, and the zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) are cross-linked with the oxidized carboxyl groups in the bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection with a porous membrane structure can be prepared.

[0036] Example 2

[0037] A photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray), the specific preparation method is as follows:

[0038] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5 g of polyvinyl pyrrolidone (PVP) and 329.25 mg of potassium ferrocyanide trihydrate were added to 100 ml of hydrochloric acid solution, stirred to dissolve to form a clear and transparent mixed solution, heated to 80° C. for 20 h, and centrifuged to obtain Prussian blue nanoparticles (PB). 0.02 g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1 g of polyvinyl pyrrolidone (PVP), stirred and dissolved in 20 ml of hydrochloric acid solution, heated to 140° C. for 4 h, and then centrifuged and washed to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB);

[0039] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinyl pyrrolidone (PVP) was dissolved in 12 ml of methanol, and 8 mg of the hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added, and after stirring to make it evenly dispersed, 20 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazole (2-Mel) were added, and after stirring for 8 h, centrifugation and washing were performed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (specific reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452 (2023) 138562);

[0040] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 112.79 mg of N-hydroxysuccinimide (NHS) were stirred at room temperature to obtain carboxyl-activated powder, and an acetic acid solution of natural polysaccharides (the acetic acid solution of natural polysaccharides contained 1 g of bacterial cellulose and 1 g of polysaccharide (CS)) was added and stirred at room temperature for 18 h to form a BC-CS solution. After the reaction was completed, the solution was dialyzed and 1×10 -4 g The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped, stirred overnight at room temperature, and the zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) are cross-linked with the oxidized carboxyl groups in the bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection with a porous membrane structure can be prepared.

[0041] Example 3

[0042] A photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray), the specific preparation method is as follows:

[0043] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5 g of polyvinyl pyrrolidone (PVP) and 329.25 mg of potassium ferrocyanide trihydrate were added to 100 ml of hydrochloric acid solution, stirred to dissolve to form a clear and transparent mixed solution, heated to 80° C. for 20 h, and centrifuged to obtain Prussian blue nanoparticles (PB). 0.02 g of Prussian blue nanoparticles (PB) were weighed and mixed with 0.1 g of polyvinyl pyrrolidone (PVP), stirred and dissolved in 20 ml of hydrochloric acid solution, heated to 140° C. for 4 h, and then centrifuged and washed to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB);

[0044] (2) Preparation of ZIF-8@H-MPB composite nanoparticles (ZHP): 60 mg of polyvinyl pyrrolidone (PVP) was dissolved in 12 ml of methanol, and 8 mg of the hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) was added, and after stirring to make it evenly dispersed, 25.6 g of zinc nitrate hexahydrate and 3.5 g of 2-methylimidazole (2-Mel) were added. After stirring for 12 h, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles (ZHP) (specific reference Prussian Blue@Zeolitic imidazolate framework composite toward solar-triggered biodecontamination, Chemical Engineering Journal 452 (2023) 138562);

[0045] (3) Preparation of photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray): 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 112.79 mg of N-hydroxysuccinimide (NHS) were stirred at room temperature to obtain carboxyl-activated powder, and an acetic acid solution of natural polysaccharides (the acetic acid solution of natural polysaccharides contained 1 g of bacterial cellulose and 1 g of polysaccharide (CS)) was added and stirred at room temperature for 24 h to form a BC-CS solution. After the reaction was completed, the solution was dialyzed and 1×10 -4g The ZIF-8@H-MPB composite nanoparticles (ZHP) prepared in step (2) are doped, stirred overnight at room temperature, and the zinc ions released by the ZIF-8@H-MPB composite nanoparticles (ZHP) are cross-linked with the oxidized carboxyl groups in the bacterial cellulose. After drying at room temperature, a photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection with a porous membrane structure can be prepared.

[0046] Comparative Example 1

[0047] A BC-CS composite membrane (0.33% BC:CS), the specific preparation method is as follows:

[0048] 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 112.79 mg of N-hydroxysuccinimide (NHS) were added and stirred at room temperature to obtain carboxyl-activated powder, and an acetic acid solution of natural polysaccharides (the acetic acid solution of natural polysaccharides contained 1 g of bacterial cellulose and 0.5 g of chitosan (CS) mixed by amide reaction) was added, and stirred at room temperature overnight to form a BC-CS solution. After the reaction was completed, dialyzed, stirred at room temperature overnight, and dried at room temperature to prepare a BC-CS composite membrane (0.33% BC:CS).

[0049] Comparative Example 2

[0050] A BC-CS composite membrane (0.67% BC:CS), the specific preparation method is as follows:

[0051] The "acetic acid solution of natural polysaccharides containing 1g of bacterial cellulose and 0.5g of chitosan (CS) are mixed by amide reaction" in Comparative Example 1 is modified to "acetic acid solution of natural polysaccharides containing 1g of bacterial cellulose and 1g of chitosan (CS) are mixed by amide reaction", and the rest is the same as Comparative Example 1.

[0052] Comparative Example 3

[0053] A BC-CS composite membrane (1.33% BC:CS), the specific preparation method is as follows:

[0054] The "acetic acid solution of natural polysaccharides containing 1g bacterial cellulose and 0.5g chitosan (CS) are mixed through amide reaction" in Comparative Example 1 is modified to "the acetic acid solution of natural polysaccharides containing 1g bacterial cellulose and 2g chitosan (CS) are mixed through amide reaction", and the rest is the same as Comparative Example 1.

[0055] Comparative Example 4

[0056] A BC-CS@HP antibacterial spray, the specific preparation method is as follows:

[0057] (1) Preparation of hollow mesoporous Prussian blue nanoparticles (H-MPB): 7.5 g of polyvinyl pyrrolidone (PVP) and 329.25 mg of potassium ferrocyanide trihydrate were added to 100 ml of hydrochloric acid solution, stirred to dissolve to form a clear and transparent mixed solution, heated to 80° C. for 20 h, and centrifuged to obtain Prussian blue nanoparticles (PB), which were further mixed with 0.1 g of polyvinyl pyrrolidone (PVP) and stirred to dissolve in 20 ml of hydrochloric acid solution, heated to 140° C. for 4 h, and then centrifuged and washed to obtain hollow mesoporous Prussian blue nanoparticles (H-MPB);

[0058] (2) Preparation of BC-CS@HP: 0.016 g of TEMPO-oxidized bacterial cellulose dispersion (TO-BC), 228.2 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC), and 112.79 mg of N-hydroxysuccinimide (NHS) were stirred at room temperature to obtain a carboxyl-activated powder, and an acetic acid solution of a natural polysaccharide (the acetic acid solution of a natural polysaccharide contains 0.67 g of bacterial cellulose and 1.33 g of polysaccharide (CS) mixed by amide reaction) was added and stirred at room temperature overnight to form a BC-CS solution. After the reaction was completed, the solution was dialyzed and 1×10 -5 g The hollow mesoporous Prussian blue nanoparticles (H-MPB) prepared in step (1) are doped, and the hollow mesoporous Prussian blue nanoparticles (H-MPB)-doped BC-CS@HP antibacterial spray is obtained by stirring overnight at room temperature.

[0059] Performance Testing

[0060] Figure 1 A is the tensile properties of different BC-CS composite films prepared in the comparative examples after film formation, and B is the tensile properties of chitosan (CS), the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) prepared in Example 1, and the BC-CS composite film (BC-CS) prepared in Comparative Example 2 after film formation. Figure 1As shown in Figure A, the tensile fracture test was carried out on the BC-CS composite membranes at three chitosan ratios. The results of the stress-strain curves show that although the stress of the 0.33% BC-CS composite membrane is relatively high, the elongation at fracture is 0, which is relatively brittle; the stress of the 0.67% BC-CS composite membrane can reach 52.58Kpa and has good ductility; the stress of the 1.33% BC-CS composite membrane is only 12.75Kpa, and the fracture strain is also lower than that of the 0.67% BC-CS composite membrane. Therefore, the 0.67% BC-CS composite membrane has better tensile strength in the comprehensive comparison of the three different chitosan ratios. In addition, the stress of CS is high but the fracture strain is poor. Compared with pure CS, the addition of bacterial cellulose (BC) reduces the stress to 24.30KPa but effectively improves the ductility of the composite membrane. The addition of ZHP nanoparticles releases some zinc ions, which further promotes the cross-linking degree of the BC-CS membrane, thereby improving its tensile properties.

[0061] Figure 2 To compare the adhesion properties of different BC-CS composite films prepared in Examples 1 to 3 after film formation. Figure 2 It can be seen that the adhesion between the BC-CS composite film with different proportions and the pig skin shows that the adhesion between the 0.67% BC-CS composite film and the pig skin can reach up to 22.08 KPa. This result further verifies that the 0.67% BC-CS has better cross-linking effect and better mechanical properties.

[0062] Figure 3 To compare the swelling properties of different BC-CS composite membranes prepared in Examples 1 to 3 after film formation. Figure 3 It can be seen that the swelling rate of 1.33% BC-CS can reach 326.45%, proving that the material has a certain swelling rate that can ensure the absorption of wound exudate while avoiding membrane damage.

[0063] Figure 4 The antibacterial properties of ZIF-8@H-MPB composite nanoparticles (ZHP) and hollow mesoporous Prussian blue (H-MPB) prepared in Example 1 at different concentrations under visible light. Figure 4 It can be seen that ZIF-8@H-MPB composite nanoparticles (ZHP) have excellent antibacterial properties at a nanoparticle concentration of 300 μg / mL, and the antibacterial rate under visible light can reach 99.86%.

[0064] Figure 5 The color indication effect after film formation is compared between the modified H-MPB nanoparticles (BC-CS@HP) prepared in Example 4 and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) in Example 3. Figure 5It can be seen that the modified H-MPB nanoparticles and the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) both have color indication capabilities and can undergo reduction reactions with bacterial metabolism and be reduced to white.

[0065] In addition, the above-mentioned performance test was also performed on the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) prepared in the above-mentioned Examples 2 and 3, and the results were similar to the performance of the photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) in Example 1. Both have good antibacterial and wound healing abilities, and are multifunctional skin dressings that can be triggered by sunlight and monitored in real time, and have dual functions of monitoring and treatment.

[0066] In summary, the present invention discloses a photocatalytic antibacterial spray for skin wound infection and a preparation method thereof. The photocatalytic antibacterial spray for skin wound infection (BC-CS@ZHP antibacterial spray) is mainly prepared by using natural polysaccharide and ZIF-8@H-MPB composite nanoparticles (ZHP). The multifunctional skin dressing has the functions of antibacterial, promoting wound healing, triggering by sunlight and real-time monitoring, and has the dual functions of monitoring and treatment. On the one hand, when the spray is sprayed on the wound, it can fit on the skin surface to form a protective film covering the wound, effectively reducing the external stimulation of the wound, and the Zn released by the nanoparticles can effectively reduce the external stimulation of the wound. 2+ Promote wound healing and regeneration. At the same time, ZIF-8@H-MPB nanoparticles generate ROS under the triggering of sunlight to enhance antibacterial ability, which can effectively treat wound infection. On the other hand, the metabolic process of bacteria will affect the redox reaction of Prussian blue to produce optical changes visible to the naked eye, thereby achieving the effect of monitoring, and the dressing can also be regularly replaced according to the change of the color of the dressing. In addition, the photocatalytic antibacterial spray (BC-CS@ZHP antibacterial spray) for skin wound infection disclosed in the present invention has the following advantages: (1) The optical changes produced by the reduction reaction of Prussian blue nanoparticles (PB) and bacterial metabolism used in the preparation process can realize the dynamic monitoring of the antibacterial process; (2) The prepared spray form can better adapt to irregular wound shapes compared with traditional dressings such as hydrogels and gauze; (3) The prepared antibacterial spray uses sunlight to generate ROS to achieve high-efficiency antibacterial, and the zinc ions released by the nanoparticles form metal coordination bonds with the oxidized bacterial cellulose to improve its mechanical properties after film formation.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a photocatalytic antibacterial spray for skin wound infection, characterized in that: The preparation method comprises the following steps: A TEMPO-oxidized bacterial cellulose dispersion, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide are added and stirred at room temperature to obtain a carboxyl activation solution, and an acetic acid solution of a natural polysaccharide is added and stirred at room temperature for 18 to 24 hours to react to form a BC-CS solution. After the reaction is completed, the solution is dialyzed and the ZIF-8@H-MPB composite nanoparticles prepared in step (2) are added and stirred at room temperature overnight to prepare a photocatalytic antibacterial spray for skin wound infection.

2. The preparation method according to claim 1, characterized in that: The ZIF-8@H-MPB composite nanoparticles were prepared according to the following method: (1) Preparation of hollow mesoporous Prussian blue nanoparticles: adding polyvinyl pyrrolidone and potassium ferrocyanide trihydrate to a hydrochloric acid solution, stirring to dissolve them to form a clear and transparent mixed solution, heating the solution for reaction, and centrifuging to obtain Prussian blue nanoparticles, further mixing the solution with polyvinyl pyrrolidone, stirring to dissolve the solution in a hydrochloric acid solution, heating the solution for reaction, and centrifuging to obtain hollow mesoporous Prussian blue nanoparticles; (2) Preparation of ZIF-8@H-MPB composite nanoparticles: polyvinyl pyrrolidone was dissolved in methanol, and the hollow mesoporous Prussian blue nanoparticles prepared in step (1) were added, and zinc nitrate hexahydrate and 2-methylimidazole were added after stirring to make them dispersed evenly. After stirring for 6 to 12 hours, the mixture was centrifuged and washed to obtain ZIF-8@H-MPB composite nanoparticles.

3. The preparation method according to claim 2, characterized in that: In step (1), the mass molar ratio of polyvinyl pyrrolidone to potassium ferrocyanide trihydrate is 7.5:1, g:mmol, and the mass ratio of Prussian blue nanoparticles to polyvinyl pyrrolidone is 1:

5.

4. The preparation method according to claim 2, characterized in that: In step (1), during the preparation of Prussian blue nanoparticles, the heating reaction temperature is 80° C. and the time is 20 h, and the reaction temperature of Prussian blue nanoparticles and polyvinyl pyrrolidone is 140° C. and the time is 4 h.

5. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of polyvinyl pyrrolidone, hollow mesoporous Prussian blue nanoparticles, zinc nitrate hexahydrate and 2-methylimidazole is 60:8:12.8-25.6:3.

5.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the TEMPO-oxidized bacterial cellulose dispersion, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in the carboxyl activation solution is 16:228.2:112.

79.

7. The preparation method according to claim 1, characterized in that: The volume mass ratio of the natural polysaccharide in the carboxyl activation solution and the chitosan acetic acid solution to the ZIF-8@H-MPB composite nanoparticles is 100-120:0.5-2:1x10 -4 ~5x10 -4 , ml:g:g.

8. The preparation method according to claim 1, characterized in that: The natural polysaccharide is any one or both of bacterial cellulose and chitosan.

9. The photocatalytic antibacterial spray for skin wound infection prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the photocatalytic antibacterial spray for skin wound infection according to claim 9 in the aspects of antibacterial and repair of skin wounds.

Citation Information

Patent Citations

  • Bacterial cellulose / chitosan composite gel and preparation thereof, and application of composite gel in body surface wound surface healing

    CN103463124A

  • Bimetallic organic framework antibacterial nanoparticles with photothermal effect, and preparation method and application thereof

    CN107823220A

  • Prussian blue-like nano material as well as preparation method and application thereof

    CN112402449A

  • Metal organic framework ZIF-8 wrapped prussian blue loaded quercetin nanoparticles, preparation method and application

    CN112870191A

  • Preparation method of HMPB, Prussian-blue-based fluorescent probe and preparation method of Prussian-blue-based fluorescent probe

    CN114163843A